The effect of exercises using repetitive training method on special strength and concentration (LDH-CPK) Achievement among young weightlifters - FARHAN ALWAN, HASSAN; KADHIM IRHAYYIM, THAMER; ALI JAAFAR MOHAMMED, ABD (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in preparing a training method in the iterative training method and knowing the extent of its effects on the muscles through measuring (LDH-CPK). In addition to its effect on achievement in the snatching high for the young category. The research problem is reflected in a better performance in developing and improving the special strength and less harmful to the muscles through training and enzymatic measurement (LDH-CPK), This is accompanied by the improvement in achievement in weightlifting. The research aims to identify the differences between the pre and post measurements in the special strength and concentration (LDH-CPK) and the achievement in the snatching height, as well as by preparing exercises in a repetitive training method, the researcher used the experimental approach, and the research community determined the weightlifters of the Port and South Oil Club of the young category with a weight of (62 kg). The research community reached (9) fourers. The researcher chose (7) fourers and made homogeneity for the research sample. The most important conclusions are the effect of repetitive training on muscle strength and enzymatic (CPK-LDH), which reflected its positive effects on achievement, and the researcher recommends emphasizing the use of modern training methods and methods while taking into account the emphasis on examining enzymes before and after training.